Th17 Cells in Periodontitis and Its Regulation by A20 - Huang, Ning; Dong, Hao; Luo, Yuqi; Shao, Bin (Frontiers in Immunology, 2021)
Periodontitis is a prevalent chronic disease that results in loss of periodontal ligament and bone resorption. Triggered by pathogens and prolonged inflammation, periodontitis is modulated by the immune system, especially pro-inflammatory cells, such as T helper (Th) 17 cells. Originated from CD4+ Th cells, Th17 cells play a central role for they drive and regulate periodontal inflammation. Cytokines secreted by Th17 cells are also major players in the pathogenesis of periodontitis. Given the importance of Th17 cells, modulators of Th17 cells are of great clinical potential and worth of discussion. This review aims to provide an overview of the current understanding of the effect of Th17 cells on periodontitis, as well as a brief discussion of current and potential therapies targeting Th17 cells. Lastly, we highlight this article by summarizing the causal relationship between A20 (encoded by TNFAIP3), an anti-inflammatory molecule, and Th17 cell differentiation.